Embracing a rational approach toward “the ranking rush” - Wang, Rong (Journal of International Students, 2026)
This research briefly examines the growing influence of major global university rankings, such as QS, THE, ARWU, and U.S. News & World Report, on institutional strategies. Using document analysis and a narrative review, this study investigates the "ranking-mania" driven by perceived links between league tables and institutional reputation. Comparative mapping of ranking methodologies shows that reputation and research indicators currently dominate the landscape, whereas indicators of student outcomes remain minimal. These findings suggest that current metrics often fail to reflect the diverse needs of domestic and international students. Consequently, the study recommends that institutions move beyond the "ranking rush" to adopt a rational, mission-centric strategy that prioritizes substantive institutional improvements over the pursuit of fluctuating external metrics.